Peran Allah dan Sidang Ilahi dalam Penciptaan Manusia Berdasarkan Kejadian 1:26-27 - Marbun, Tolop (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This research aims to analyze the scriptural passage of Genesis 1:26, which outlines a declaration for the creation of human beings within the divine counsil, and Genesis 1:27 is the proof that direct involvement of God in the creation of humans without the involvement of the court's constituents. This method emplyed in this reseach is text analysis study which integrates various analytical approaches such as context analysis, syntactic analysis, verbal analysis, and theological analysis. The pronoun “us” in verse 26 has led three disticnt interpretation.The initial interpretation, the verse pertains to the concept of the Trinity. According to the second interpretation, it is believed that God communicated with individuals throughout human history. The third interpretations that verse 26 pertains to a Devine council, while verse 27 exclusively attributes the creation of humanity by God Himself. The study's results indicate that Genesis 1:26 affirms the Divine council 's plan to bring about the creation of humans, while verse 27 denotes that God singularly executed the creation of humans without the involvement of the Divine council.